A Longitudinally Extensive Spinal Cord Lesion Restricted to Gray Matter in an Adolescent Male - Golub, Danielle; Williams, Faith; Wong, Taylor; Iyengar, Nishanth; Jolley, Hannah; Sabadiah, Sakinah; Rhee, David; Gold-von Simson, Gabrielle (Frontiers in Neurology, 2019)
Longitudinally extensive spinal cord lesions (LECL) restricted to gray matter are poorly understood as are their neurodevelopmental repercussions in children. We herein report the critical case of a 13-year-old male presenting with progressive quadriparesis found to have cervical LECL restricted to the anterior horns. Challenged with a rare diagnostic dilemma, the clinical team systematically worked through potential vascular, genetic, infectious, rheumatologic and paraneoplastic diagnoses before assigning a working diagnosis of acute inflammatory myelopathy. Nuanced consideration of and workup for both potential ischemic causes (arterial dissection, fibrocartilaginous embolism, vascular malformation) and specific inflammatory conditions including Transverse Myelitis, Neuromyelitis Optica Spectrum Disorders (NMOSD), Multiple Sclerosis (MS), Acute Disseminated Encephalomyelitis (ADEM), and Acute Flaccid Myelitis (AFM) is explained in the context of a comprehensive systematic review of the literature on previous reports of gray matter-restricted longitudinally extensive cord lesions in children. Treatment strategy was ultimately based on additional literature review of treatment-refractory acute inflammatory neurological syndromes in children. A combination of high-dose steroids and plasmapheresis was employed with significant improvement in functional outcome, suggesting a potential benefit of combination immune-modulatory treatment in these patients. This case furthermore highlights quality clinical reasoning with respect to the elusive nature of diagnosis, nuances in neuroimaging, and multifocal treatment strategies in pediatric LECL.